Image Analysis and Processing - ICIAP 2022 21st International Conference, Lecce, Italy, May 23-27, 2022, Proceedings, Part I - Sclaroff, Stan.; Distante, Cosimo; Leo, Marco; Farinella, Giovanni M.; Tombari, Federico (Cham : Springer International Publishing : Imprint: Springer, 2022)
The proceedings set LNCS 13231, 13232, and 13233 constitutes the refereed proceedings of the 21st International Conference on Image Analysis and Processing, ICIAP 2022, which was held during May 23-27, 2022, in Lecce, Italy, The 168 papers included in the proceedings were carefully reviewed and selected from 307 submissions. They deal with video analysis and understanding; pattern recognition and machine learning; deep learning; multi-view geometry and 3D computer vision; image analysis, detection and recognition; multimedia; biomedical and assistive technology; digital forensics and biometrics; image processing for cultural heritage; robot vision; etc.
Brave New Ideas -- Biomedical and Assistive Technology -- Multimedia -- Deep Learning -- Image Processing for Cultural Heritage -- Robot Vision.
Keywords: Computer vision; Application software; Education-Data processing; Social sciences-Data processing; Machine learning; Pattern recognition systems; Computer Vision; Computer and Information Systems Applications; Computers and Education; Computer Application in Social and Behavioral Sciences; Machine Learning; Automated Pattern Recognition